(3+1)‐Incommensurately modulated crystal structure of Cs3ScSi6O15. Issue 1 (1st February 2016) - Hejny, Clivia; Kahlenberg, Volker; Schmidmair, Daniela; Dabić, Predrag
Abstract : The structure of Cs3 ScSi6 O15 has been solved and refined as an incommensurately modulated crystal structure in (3+1)‐dimensional superspace. Large positional modulations of the constituting atoms give rise to satellite reflections up to the fourth order. Abstract : Single‐crystal X‐ray diffraction of Cs3 ScSi6 O15 shows the presence of main reflections and satellite reflections up to the fourth order along thec* direction. The (3+1)‐dimensional incommensurately modulated structure was solved in superspace group [ a = 13.861 (1), c = 6.992 (1) Å, V = 1163.4 (2) Å 3 ] with a modulation wavevectorq = 0.14153 (2)c* . Refinement of three modulation waves for positional and anisotropic displacement parameter values for all atoms converged to R obs values for all, main and satellite reflections of first, second and third order of 0.0200, 0.0166, 0.0181, 0.0214 and 0.0303, respectively. Cs3 ScSi6 O15 forms a mixed tetrahedral–octahedral framework with prominent six‐membered rings of [SiO4 ]‐tetrahedra interconnected by [ScO6 ]‐octahedra. Apart from Sc, all atoms are strongly affected by positional modulation with maximum atomic displacements of up to 0.93 Å causing rigid polyhedral arrangements to perform tilt and twist movements relative to each other, such as a rotation of the Sc‐octahedra around the ‐axis by over 38°. Cs has an irregular coordination environment; however, considering distances up to 3.5 Å, the bond‐valence sum changes by no more than 0.02 as a function of t and thus overall kept at a level of ca 1.075.